Managing External Radiation Exposure and Area Zoning in Industrial Radiography Training: A Case Report - Arifin, Gusti Sultan; Atriana, Dinda; Abadha, Aksin Maula; Pribadi, Ari Prayogo; Promkhum, Dangfun; Fauzi, Desta Zul (ASEAN Journal of Disaster Health Management (AJDHM), 2026)
Industrial radiography poses significant risks of external radiation exposure, particularly in training and operational environments. Effective radiation protection requires comprehensive understanding and application of key safety principles, including time, distance, shielding, and radiation zone identification. This study aims to evaluate external radiation exposure control through a series of practical activities conducted at the Vocational of Nuclear Technology X. Twenty-one participants performed tasks using gamma radiation sources to identify potential hazards, determine control and supervision areas, evaluate dose rate variations with distance and time, and assess the effectiveness of shielding materials. Data were collected through direct measurement and theoretical calculations and analyzed thematically. Findings confirmed that increasing distance and reducing exposure time significantly lowered dose rates, while shielding materials such as lead and concrete effectively attenuated gamma radiation. Conclusions: The study concludes that practical, scenario-based training reinforces technical competencies and safety culture among trainees. The results offer a valuable reference for students, researchers, and radiation workers in understanding external radiation management within radiographic practices.